The Role of Artificial Intelligence (AI) in Medicine - Archambault, Olivia (Trinity Student Medical Journal, 2025)
The article discusses the impact and potential of artificial intelligence (AI) in medicine, focusing on ChatGPT and similar AI tools in diagnostics and clinical practice. This theme is explored in an interview with Dr Bhambra, a Canadian general practitioner (GP) who has a research interest in AI technology. The ability for AI to streamline administrative tasks and diagnostics is highlighted, thus, improving patient care and physician efficiency. Implementation challenges include system resistance, regulatory obstacles, and the need for human oversight to ensure ethical and safe use. AI is unlikely to replace doctors but will likely enhance healthcare delivery.